Examining hindrance factors for hiring people with disabilities (PWDs) in Malaysia: employer’s perspectives - Omar, Muhd Khaizer; Li, Yu Can; Jamaluddin, Fadhilah; Mat Rashid, Abdullah; Saripan, M Iqbal; Mohd Puad, Mohd Hazwan; Mahazir Ismail, Irwan; Mohammad Hussain, Mohd Azlan (Research and Scientific Innovation Society, 2024)
People with disabilities (PWDs) in Malaysia face significant barriers to employment despite existing laws and policies aimed at promoting their inclusion in the workforce. This study sought to identify the key factors that hinder employers from hiring PWDs, which contributes to their ongoing marginalization in the job market. A descriptive quantitative survey was conducted with 148 employers, and Binary Logistic Regression was used to analyze the data. The study identified five major barriers: the nature of the work, a lack of qualified candidates with disabilities, the perceived high cost of accommodating disabilities, concerns about increased healthcare costs, and a lack of knowledge or information among employers. To address these challenges, the study suggests that more comprehensive policies, targeted employer education, and better support systems are necessary. The findings underscore the importance of tackling these barriers to enhance employment opportunities for PWDs and improve their quality of life in Malaysia. The study concludes that without addressing these issues, the inclusion of PWDs in the workforce will remain problematic.